Evolvulus alsinoides methanolic extract triggers apoptosis in HepG2 cells - Induja MP; Ezhilarasan Devaraj; Ashok Vardhan Nandigam (Mashhad University of Medical Sciences, 2018)
Objective: The objective of the present study was to evaluate the cytotoxic potentials of Evolvulus alsinoides in human hepatoma HepG2 cells. Materials and Methods: HepG2 cells were treated with methanolic extract of E. alsinoides at 20, 40 and 80 µg/ml for 24 hr and cytotoxic effect was analyzed by MTT assay. The apoptosis rate was investigated by Hoechst 33342 and annexin V/propidium iodide staining. Mitochondrial membrane potential was evaluated by rhodamine staining. Also, the expression of catenin - β 1 protein was analyzed by western blotting. Results: E. alsinoides methanolic extract treatment caused significant cytotoxicity in HepG2 cells in a concentration-dependent manner.Dual staining assayconfirmed the presence of early and late apoptotic cells only in extract-treated groups. Plant extract treatment also caused nuclear fragmentation and chromatin condensation in HepG2 cells. Mitochondrial membrane potential also reduced upon E. alsinoides treatments.This treatment also modulated the catenin - β 1 protein expression. Conclusion:In this study, we demonstrated theproapoptotic potential E. alsinoides in HepG2 cells; thus, this plant may be beneficial in the treatment of liver cancer.